Mechanical properties of graphene and graphene-based nanocomposites - Papageorgiou, D. G.; Kinloch, I. A.; Young, R.
In this present review, the current status of the intrinsic mechanical properties of the graphene-family of materials along with the preparation and properties of bulk graphene-based nanocomposites is thoroughly examined. The usefulness of Raman spectroscopy for the characterization and study of the mechanical properties of graphene flakes and their composites is clearly exhibited. Furthermore, the preparation strategies of bulk graphene-based nanocomposites are discussed and the mechanical properties of nanocomposites reported in the literature are analysed. In particular, through the analyse of several hundred literature papers on graphene composites, we have found a unique correlation between the filler modulus, derived from the rule of mixtures, and the composite matrix. This correlation is found to hold true across a wide range of polymer matrices and thus suggests that the common assumption that the filler modulus is independent of the matric is incorrect, explaining the apparent under performance of graphene in some systems. The presence of graphene even at very low loadings can provide significant reinforcement to the final material, while the parameters that affect the nanocomposite strongly are thoroughly reviewed. Finally, the potential applications and future perspectives are discussed with regard to scale up capabilities and possible developments of graphene-based nanocomposite materials.
Keywords: GRAPHENE; NANOCOMPOSITES; MECHANICAL PROPERTIES; RAMAN SPECTROSCOPY MICROMECHANICS; REINFORCEMENT